2018
DOI: 10.3847/1538-4357/aacb34
|View full text |Cite
|
Sign up to set email alerts
|

The X-Ray Luminosity Function of Ultraluminous X-Ray Sources in Collisional Ring Galaxies

Abstract: Ring galaxies are fascinating laboratories: a catastrophic impact between two galaxies (one not much smaller than the other) has produced fireworks especially in the larger one, when hit roughly perpendicularly to the plane. We analyze the point sources, produced by the starburst episode following the impact, in the rings of seven galaxies and determine their X-ray luminosity function (XLF). In total we detect 63 sources, of which 50 have luminosity L X ≥ 10 39 erg s −1 , classifying them as ultra luminous X-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 100 publications
1
21
1
Order By: Relevance
“…The differential forms of observed XLFs (𝑑𝑁/𝑑𝐿) are often fitted with power-laws, or variants such as broken or exponential cutoff power-laws (see Grimm et al 2003;Swartz et al 2011;Mineo et al 2012;Wang et al 2016;Wolter et al 2018;Kovlakas et al 2020). In Figure 3 we plot a subset of the differential forms of our synthetic XLFs versus the best fit models from Wang et al (2016) who used Chandra observations of 343 galaxies (totalling 4970 sources, 218 of which are ULXs) to create differential XLFs.…”
Section: Modelling the Xlfmentioning
confidence: 99%
“…The differential forms of observed XLFs (𝑑𝑁/𝑑𝐿) are often fitted with power-laws, or variants such as broken or exponential cutoff power-laws (see Grimm et al 2003;Swartz et al 2011;Mineo et al 2012;Wang et al 2016;Wolter et al 2018;Kovlakas et al 2020). In Figure 3 we plot a subset of the differential forms of our synthetic XLFs versus the best fit models from Wang et al (2016) who used Chandra observations of 343 galaxies (totalling 4970 sources, 218 of which are ULXs) to create differential XLFs.…”
Section: Modelling the Xlfmentioning
confidence: 99%
“…In few cases they are associated with older stellar populations in elliptical galaxies (Feng & Kaaret 2008, Roberts et al 2008. A large number of ULXs has been found also in the young and star forming rings of ring galaxies (Wolter et al 2018). Many of them are located in or close to young O-B associations (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The smooth connection with the lower luminosity sources and the slope of the XLF are consistent with our hypothesis. This is also shown by the XLF of both a large number of ULXs collected in the rings of seven collisional RiGs (Wolter et al 2018) and those in the collection of nearby galaxies (Swartz et al 2011) observed by Chandra, which yield a similar number of ULXs and consistent results between each other, even if the RiGs have a possible excess at high luminosity. The combination of many galaxies relies on the assumption that we are witnessing a single burst of star formation in each galaxy, with a reasonable short age (possibly less than 100 Myr as per the simulations of Renaud et al 2018), close to the formation time of HMXB, and that the spread in metallicity is not large.…”
Section: The X-ray Luminosity Function Of Ulxsmentioning
confidence: 58%